$${\frac{{\mathtt{5}}}{{\mathtt{6}}}} = {\frac{{\mathtt{1}}}{{\mathtt{3}}}}{\mathtt{\,\small\textbf+\,}}{\mathtt{d}}$$

$${\mathtt{5}} = {\frac{{\mathtt{1}}}{{\mathtt{3}}}}{\mathtt{\,\times\,}}{\mathtt{6}}{\mathtt{\,\small\textbf+\,}}{\mathtt{6}}{d}$$

$${\mathtt{5}} = {\mathtt{2}}{\mathtt{\,\small\textbf+\,}}{\mathtt{6}}{d}$$

$${\mathtt{5}}{\mathtt{\,-\,}}{\mathtt{2}} = {\mathtt{2}}{\mathtt{\,\small\textbf+\,}}{\mathtt{6}}{d}{\mathtt{\,-\,}}{\mathtt{2}}$$

$${\mathtt{3}} = {\mathtt{6}}{d}$$

$${\frac{{\mathtt{3}}}{{\mathtt{6}}}} = {\frac{{\mathtt{6}}{d}}{{\mathtt{6}}}}$$

$${\mathtt{d}} = {\frac{{\mathtt{1}}}{{\mathtt{2}}}}$$

hope it helped :)